Genetic divergence for crop improvement in Sesame (Sesamum indicum L.): Genetic divergence for crop improvement in Sesame (Sesamum indicum L.) - D BHARATHI; K NAVYA JYOTHI; C KIRAN KUMAR REDDY (Journal of Oilseeds Research, 2023)
Genetic divergence in 92 accessions of sesame was evaluated by using Mahalanobis D2 statistics to identify the potential parents in the hybridization programme. The genotypes were grouped into twelve clusters suggesting a considerable amount of genetic diversity in the material. The traits viz., number of primary branches per plant, number of capsules per plant and seed yield per plant contributed maximum towards the divergence and emphasis should be given for these traits for improving yield potential in sesame.